The Mediating Effect of Coping Strategies Between Psychological Capital and Small Tourism Organization Resilience: Insights From the COVID-19 Pandemic, Malaysia - Jalil, Muhammad Farhan; Ali, Azlan; Ahmed, Zeeshan; Kamarulzaman, Rashidah (Frontiers in Psychology, 2021)
In the midst of difficulty, small tourism firm owners' psychological capital has given less attention. In a COVID-19 pandemic, this research examined how psychological capital (self-efficacy, hope, optimism, and psychological resilience) affects organizational resilience. Through structural equation modeling (AMOS 21.0), 644 small tourism firm owners in Malaysia were randomly selected to investigate the relationship between psychological capital and organizational resilience, as well as the mediating effect of problem-focused and emotion-focused coping strategies on this relationship. The findings of the study supported hypothesized relationships, as the psychological capital of small tourism firm owners in Malaysia significantly affects organizational resilience. Furthermore, the study discovered that problem-focused and emotion-focused coping strategies have partial mediating effects on the association between psychological capital and organizational resilience. In the context of the small tourism businesses sector, the findings of the study have implications as the firms identify the recovery procedure in the COVID-19 pandemic.